2006
DOI: 10.1017/s1014233900002030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la variabilidad genética en ganado Criollo Colombiano mediante 12 marcadores microsatélites

Abstract: ResumenEl objetivo del presente trabajo fue estimar la variabilidad y las relaciones filogenéticas entre 6 razas de ganado criollo colombiano, cebú Brahman y la española Pirenaica, mediante el uso de 12 marcadores moleculares tipo microsatélite. El número promedio de alelos fue de 11.58 con los valores más altos para los marcadores HEL 13 y ETH 10. La heterocigocidad promedio de todas las razas fue de 0.7 y el coeficiente de endogamia fue de 0.097, con los valores más altos para la raza Romosinuano. Los mayore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
1
5
0
6
Order By: Relevance
“…The Mostrenca cattle breed from Andalusia (Spain), a proposed ancestral breed of the American Creole cattle, showed heterozygosity values between 0.29 and 0.77 (Martínez et al, 2005a). Barrera et al (2006) Recently, using the same markers used here, a separate and distinctive cluster was reported for the most southern breeds of South America: Brazilian Caracu, Argentinean Creole, Argentinean Creole cattle from Patagonia, Uruguayan Creole, and Pampa Chaqueño from Paraguay, which are rather distant from other American populations (Delgado et al, 2012). These authors suggested a close genetic relationship between populations from nearby geographical regions and their findings support the genetic distinctiveness of the Uruguayan Creole cattle.…”
Section: Microsatellitesmentioning
confidence: 52%
See 1 more Smart Citation
“…The Mostrenca cattle breed from Andalusia (Spain), a proposed ancestral breed of the American Creole cattle, showed heterozygosity values between 0.29 and 0.77 (Martínez et al, 2005a). Barrera et al (2006) Recently, using the same markers used here, a separate and distinctive cluster was reported for the most southern breeds of South America: Brazilian Caracu, Argentinean Creole, Argentinean Creole cattle from Patagonia, Uruguayan Creole, and Pampa Chaqueño from Paraguay, which are rather distant from other American populations (Delgado et al, 2012). These authors suggested a close genetic relationship between populations from nearby geographical regions and their findings support the genetic distinctiveness of the Uruguayan Creole cattle.…”
Section: Microsatellitesmentioning
confidence: 52%
“…Their adaptation to different environments allowed the expression of high levels of genetic variability, this being a source of hidden alleles of potential use in breeding programs and thus important to study and preserve (Barrera et al, 2006;De Alba Martínez, 2011). The analysis of nuclear and cytoplasmic markers, such as microsatellites and mitochondrial DNA (mtDNA), is a valuable tool to infer and assess their genetic diversity and relationships with other cattle populations of America, Europe and Africa (Armstrong et al, 2006a;Ginja et al, 2010;Delgado et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…sastre (2003) estimó un nPA de 8,54 para la raza criolla Casanareño. moreno et al (2001) reportaron un nPA de 8,9 para ganado criollo colombiano, Barrera et al (2006a), determinaron un nPA de 9,21 para ganado Caqueteño; siendo estos valores inferiores al nPA hallado por Barrera et al (2006b), en las razas criollas colombianas, que fue de 11,58 y al descrito en este estudio para la raza criolla colombiana Romosinuano que fue de 5,6. Por lo anterior se puede afirmar que, a mayor población estudiada, pueden ser detectados un mayor número de alelos con una frecuencia baja (yan y Zhang, 2004).…”
Section: Variabilidad Genéticaunclassified
“…estudios realizados por Bedoya et al (2001) en razas bovinas criollas colombianas, reportaron valores de heterocigosidad He (0,67) mayores a los encontrados en este estudio, estos valores concuerdan con un estudio realizado en la raza Casanareño, en el cual se obtuvo un valor de 0,63 (Martínez y Pérez, 2006), Barrera, et al (2006a), utilizando 12 marcadores microsatélites en seis razas criollas colombianas obtuvieron un valor de heterocigosidad de 0,77, Barrera et al (2003Barrera et al ( , 2006b (Piedrahíta et al, 2008).…”
Section: Contenido De Información Polimórfica (Pic)unclassified
See 1 more Smart Citation